Posibilidad de inserción de microalgas en el sector cárnico (2017)
Microalgae are considered a food of high nutritional value because they provide vitamins (A, B, C, E and K), minerals, essential amino acids, polysaccharides and lipids (omega-3 and omega-6), which complement the essential foods in the daily diet. The following article presents two aspects, the first is the inclusion of microalgae to add nutritional value and the second is related to the replacement of the meat product, which has the potential to generate bioactive compounds of protected nature. Among the varieties of microalgae that exist, Chlorella and Spirulina are the best known for the production of an industrial culture, whose easy acquisition has become one of the main productive and industrial advantages.